ความสัมพันธ์ระหว่างปัจจัยส่วนบุคคลและครอบครัวเข้มแข็งกับต้นทุนชีวิตของสตรีตั้งครรภ์วัยรุ่น - Lertsakornsiri, Maleewan (Naresuan University Journal: Science and Technology (NUJST); Vol 22 No 3 (2014): September-December 2014, 2014)
การตั้งครรภ์ในวัยรุ่น เป็นปัญหาที่สาคัญด้านสุขภาพอนามัยของมารดาและทารกในปัจจุบัน รวมทั้งปัญหาด้านเศรษฐกิจ และสังคม ผลกระทบที่เกิดขึ้นกับสตรีตั้งครรภ์ในวัยรุ่นมีมากมาย เช่น การคลอดทารกที่มีน้าหนักตัวน้อย ซึ่งในการวิจัยเชิงพรรณนานี้ มีวัตถุ ประสงค์เพื่อศึกษาความสัมพันธ์ระหว่างปัจจัยส่วนบุคคลและครอบครัวเข้มแข็งกับต้นทุนชีวิตของสตรีตั้งครรภ์วัยรุ่น กลุ่มตัวอย่าง คือ สตรีตั้งครรภ์ที่มีอายุระหว่าง 13-19 ปี ที่มารับบริการฝากครรภ์ที่หน่วยฝากครรภ์ โรงพยาบาลสมเด็จพระปิ่นเกล้าและโรงพยาบาลราชวิถี เป็นการเลือกกลุ่มตัวอย่างแบบเฉพาะเจาะจงจานวน 200 คน เครื่องมือวิจัยเป็นแบบสอบถามประกอบด้วยข้อมูลส่วนบุคคล ครอบครัวเข้มแข็ง และต้นทุนชีวิตของสตรีตั้งครรภ์วัยรุ่น ที่ผ่านการตรวจสอบความตรงเชิงเนื้อหาโดยผู้ทรงคุณวุฒิ 3 ท่าน ได้ค่าดัชนีความตรงเชิงเนื้อหาเท่ากับ 0.80 และค่าความเที่ยงของแบบประเมินครอบครัวเข้มแข็งเท่ากับ 0.87 และแบบสารวจต้นทุนชีวิตของสตรีตั้งครรภ์วัยรุ่นเท่ากับ 0.96 วิเคราะห์ข้อมูลโดยหาค่าความถี่ ร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน ไคสแควร์ใช้ทดสอบความสัมพันธ์ระหว่างปัจจัยส่วนบุคคลกับต้นทุนชีวิต และทดสอบความสัมพันธ์ระหว่างครอบครัวเข้มแข็งกับต้นทุนชีวิตของสตรีตั้งครรภ์วัยรุ่นด้วยสัมประสิทธิ์สหสัมพันธ์ของเพียร์สัน         ผลการวิจัย พบว่า สตรีตั้งครรภ์วัยรุ่นมีคะแนนเฉลี่ยครอบครัวเข้มแข็งโดยรวมเท่ากับ 3.05 อยู่ในระดับมาก คะแนนเฉลี่ยต้นทุนชีวิตโดยรวมเท่ากับ 2.78 อยู่ในระดับดี ผลการทดสอบความสัมพันธ์ พบว่า ปัจจัยส่วนบุคคลเฉพาะการศึกษาเท่านั้นที่มีความ สัมพันธ์กับต้นทุนชีวิตด้านพลังตัวตนของสตรีตั้งครรภ์วัยรุ่นอย่างมีนัยสาคัญทางสถิติที่ระดับ .01 (x2=22.51) สาหรับครอบครัวเข้มแข็งมีความสัมพันธ์ทางบวกระดับปานกลางกับต้นทุนชีวิตของสตรีตั้งครรภ์วัยรุ่นทุกรายด้านและโดยรวมอย่างมีนัยสาคัญทางสถิติที่ระดับ .01 (r = .47, .52, .37, .41, .47 และ .56 ตามลาดับ) ผลการศึกษาบ่งชี้ว่าหน่วยงานที่เกี่ยวข้องทั้งครอบครัว สถาบันการศึกษา สถานพยาบาล ชุมชนและสังคม ควรตระหนักถึงความสาคัญของการส่งเสริมครอบครัวเข้มแข็งและต้นทุนชีวิต เพื่อช่วยให้สตรีตั้งครรภ์วัยรุ่นมีพฤติกรรมในการดูแลสุขภาพขณะตั้งครรภ์ที่ดี ลดพฤติกรรมเสี่ยง สามารถตัดสินใจ และแก้ปัญหาได้อย่างเหมาะสม คำสำคัญ: ครอบครัวเข้มแข็ง ต้นทุนชีวิต สตรีตั้งครรภ์วัยรุ่น         These days, a pregnant adolescent is an important problem in maternal and newborn’s health including economic and social problem. Many affects occur in pregnant adolescents such as baby delivery with low birth weight. The purpose of this descriptive research was to study the relationship between personal factors as well as families’ strengths and developmental assets in pregnant adolescents. The purposive samples included 200 pregnant adolescents aged between 13-19, who visited the antenatal clinics of Rajavithi Hospital and Somdejprapinklao Hospital. The research tool was a questionnaire including personal data, families’ strengths, and developmental assets in pregnant adolescents. The questionnaire was validated by a group of 3 experts. The content validity index (CVI) of the questionnaire was 0.80, the reliability of families’ strengths and developmental assets in pregnant adolescents were 0.87 and .96, respectively. The data were analyzed by frequency, percentage, mean, standard deviation, Chi-square test for testing relationship between personal factors and developmental assets in pregnant adolescents, Pearson’s Product Moment Correlation Coefficient for testing relationship between families’ strengths and developmental assets in pregnant adolescents.         The results indicated that the average score of families’ strengths of the pregnant adolescents was high (3.05). The average score of developmental assets was 2.87, which was at a good level. The results of relation found that education aspect, which was one of the personal factors, was related with the personal image power of developmental assets at statistically significant level .01(x2=22.51). Moreover, families’ strengths were statistically significant at the positive moderate relationship with individual and overall developmental assets of pregnant adolescents at p<.01 (r=.47, .52, .37, .41, .47 and .56, respectively). The findings suggested that all the concerned parties including family, educational institution, health place, community and society should recognize the importance in promoting and enhancing families’ strengths, developmental assets, which could develop pregnant adolescents’ health care behavior, reduce the behavioral risk, make decision and solve problems appropriately. Keywords: Families’ Strengths, Development Assets, Pregnant Adolescents
Keywords: ครอบครัวเข้มแข็ง ต้นทุนชีวิต สตรีตั้งครรภ์วัยรุ่น Families’ Strengths, Development Assets, Pregnant Adolescents